2017
DOI: 10.1002/mus.25708
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in neuralgic amyotrophy: Sensitivity, spectrum of findings, and clinical correlations

Abstract: Ultrasonography may be used as a diagnostic aid in neuralgic amyotrophy, which was hitherto a clinical and electrophysiological diagnosis, and may also help in identifying potential surgical candidates. Muscle Nerve 56: 1054-1062, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
99
1
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 25 publications
3
99
1
9
Order By: Relevance
“…In this study, the majority (99%) of FCs of the median nerve proper were located at or above the elbow joint line, consistent with previous operative and imaging reports . We found posteriorly/posteromedially positioned FCs in 91% of site 1 patients, for which the mean distance was 4.7 cm proximal to the elbow joint line.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, the majority (99%) of FCs of the median nerve proper were located at or above the elbow joint line, consistent with previous operative and imaging reports . We found posteriorly/posteromedially positioned FCs in 91% of site 1 patients, for which the mean distance was 4.7 cm proximal to the elbow joint line.…”
Section: Discussionsupporting
confidence: 90%
“…Arányi et al reported a correlation between the presence of complete or incomplete constriction and clinical outcomes of nonoperative treatment in a series of PTS patients . Constriction severity was not measured in the current study, however, as we believe that the acquired spatial resolution (both with MRN and US) is currently insufficient to grade the precise severity of a constriction at the fascicular level.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…For many academic and some community practices, NMUS is a standard tool for evaluating mononeuropathies and guiding procedures . Clinical research in the field has bloomed, with NMUS demonstrating potential in the evaluation of myopathies, motor neuron diseases, inflammatory neuropathies, brachial plexopathies, nerve trauma, diaphragmatic weakness, and nerve tumors . Reinforcing the impression that NMUS is growing, a PubMed search (performed October 5, 2017) of the keywords, “nerve ultrasound,” reveals 642 publications in the year 2000 and 2,338 citations in 2016.…”
mentioning
confidence: 99%